Computational mechanics in structural engineering : recent developments - Cheng, Franklin Y.; Gu, Yuanxian; Sino-US Joint Symposium/Workshop on Recent Advancement of Computational Mechanics in Structural Engineering 1998 : Dalian, Liaoning Sheng, China) (Amsterdam ; New York : Elsevier, 1999)
The Second Sino-US Symposium Workshop on Recent Advancement of Computational Mechanics in Structural Engineering was held between May 25-28, 1998, in Dalian, China. The objectives were: to share the insights and experiences gained from recent developments in theory and practice; to assess the current state of knowledge in various topic areas of mechanics and computational methods and to identify joint research opportunities; to stimulate future cooperative research and to develop joint efforts in subjects of common needs and interests; to build and to strengthen the long-term bilateral scientific relationship between academic and professional practicing communities. Topics discussed covered the entire field of computational structural mechanics. These topics have advanced broad applications in the engineering practice of modern structural analysis, design and construction of buildings and other structures, and in natural hazard mitigation.
Chapter headings and selected papers: Keynote Presentations. Multiobjective optimum design of structures with genetic algorithm and game theory: application to life-cycle cost design (F.Y. Cheng). New solution system for plate bending (W.X. Zhong, W.A. Yao). Finite element methods based on two-scale analysis method (J.Z. Cui). Control of lateral-torsional motion of Nanjing TV transmission tower (J.C. Wu, J.N. Yang). Paper Presentations. Fast computation of stationary/non-stationary random responses of complex structures (J.H. Lin, W.X. Zhong). Solving large systems of equations on Intel-Paragon (P. Chen et al.). A review on the numerical solution schemes for localization problems (Z. Chen et al.). Recent developments in basic finite element technologies (C.A. Felippa). Parallel integration algorithms for dynamic analysis of structures in the clustered network system (J.G. Cheng et al.). Practical issues in the application of structural identification (B. Gunes et al.). Parallel PCG algorithm on distributed network by PVM (Z.C. Hou et al.). Calculation of thin plates on statistical non-uniform foundations (Yi Huang et al.). A mixed finite element for local and nonlocal plasticity (Xikui Li). A finite element model for geometrically nonlinear analysis of multi-layered composite shells (A. Masud, Choon L. Tham). Structural optimization for seismic loads: pseudo-static, response spectra and time history (K.Z. Truman). Fracture estimation: bound theorem and numerical strategy (Chang-Chun Wu et al.). ODE-oriented semi-analytic methods (Si Yuan). Index of contributers. Keyword index.
Papers from the Second Sino-US Joint Symposium/Workshop on Recent Advancement of Computational Mechanics in Structural Engineering held May 25-28, 1998, in Dalian, China.
Includes bibliographical references and indexes.
Print version record.
Keywords: Structural analysis (Engineering) -- Data processing; Computer-aided engineering; TECHNOLOGY & ENGINEERING -- Structural; Computer-aided engineering; Structural analysis (Engineering) -- Data processing; Electronic books